Safe/brave spaces in virtual exchange on sustainability - Malin Reljanovic Glimäng (University of Groningen Press, 2022)
This article explores the potential for fostering critical intercultural and global awareness through Transnational Virtual Exchange (TVE) focused on sustainability. The study is based on a lingua franca exchange between university students in Argentina, Poland, and Sweden. A qualitative content analysis of student e-portfolios unveiled reflective dimensions construed here as safe/brave spaces, echoing Andreotti's (2006) notion of soft versus critical global citizenship education. Using theories of critical interculturality and third space, the analysis shows potential for developing participants' critical reflection through TVE. However, the findings also reveal how in-depth reflection is often a lonely endeavor, overshadowed by project tasks that might unintentionally steer learners toward safe topics and consensus. So far, critical reflection is an underexplored area in empirical Virtual Exchange (VE) research. Student voices in this study bring to the fore questions regarding what it means to approach global citizenship education critically through online collaboration. The findings have implications for future design of VE projects where the focus is on social change through action-oriented tasks, but where critical and dialogic reflection after the completion of a pedagogical task is the salient part.